2011
DOI: 10.1177/0022034511399908
|View full text |Cite
|
Sign up to set email alerts
|

Saliva/Pathogen Biomarker Signatures and Periodontal Disease Progression

Abstract: The purpose of this study was to determine the role of saliva-derived biomarkers and periodontal pathogens during periodontal disease progression (PDP). One hundred human participants were recruited into a 12-month investigation. They were seen bi-monthly for saliva and clinical measures and bi-annually for subtraction radiography, serum and plaque biofilm assessments. Saliva and serum were analyzed with protein arrays for 14 pro-inflammatory and bone turnover markers, while qPCR was used for detection of biof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
202
1
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 175 publications
(221 citation statements)
references
References 24 publications
8
202
1
7
Order By: Relevance
“…63 It has been proposed that not only host-derived factors should be analysed in the saliva but also oral pathogens to be able to predict periodontitis, since it is a multifactorial disease. 64 Indeed, investigators have found that higher salivary of levels of Porphyromonas gingivalis, Tannerella forsythia and Prevotella intermedia were found in individuals with progressive periodontitis. 65 This phenomenon has also been noted by a recent study, which shows that the combination of salivary P. gingivalis quantity with host specific pathogen response would be useful in diagnosing periodontitis with high accuracy.…”
Section: Periodontal Diseasesmentioning
confidence: 99%
“…63 It has been proposed that not only host-derived factors should be analysed in the saliva but also oral pathogens to be able to predict periodontitis, since it is a multifactorial disease. 64 Indeed, investigators have found that higher salivary of levels of Porphyromonas gingivalis, Tannerella forsythia and Prevotella intermedia were found in individuals with progressive periodontitis. 65 This phenomenon has also been noted by a recent study, which shows that the combination of salivary P. gingivalis quantity with host specific pathogen response would be useful in diagnosing periodontitis with high accuracy.…”
Section: Periodontal Diseasesmentioning
confidence: 99%
“…Different molecules act in this scenario, reflecting periodontal bone loss activity and susceptibility. However, because this is a highly complex disease, it is unlikely that a single biomarker for disease detection and prediction can be found (Kinney et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Human saliva contains a large number of proteins that comes from salivary glands and GCF, and can be used for diagnosis [10,11] . Saliva could be potentially used to monitor periodontal disease progression or stability [12,13]. In periodontal disease, bacterial infection stimulates local inflammation and alveolar bone loss are characters of this disease [14].…”
Section: Introductionmentioning
confidence: 99%